PERUBAHAN SOSIAL EKONOMI DAN EKOLOGI DALAM UPAYA PENGELOLAAN SUB DAERAH ALIRAN SUNGAI PUSUR DI KABUPATEN KLATEN - Yuanita Dwi Hapsari; Ghina Reftantia; Deni Aries Kurniawan; Maulida Masyitoh; Triana Rahmawati (Yayasan Literasi Sains Indonesia, 2025)
This study examines the social, economic, and ecological transformations in the management of the Pusur Sub-Watershed (Sub DAS) in Klaten Regency, with a focus on the distribution of actor roles and the contribution of local institutional arrangements. The research adopts a qualitative approach, utilizing data collection methods such as observation, in-depth interviews, and documentation across the upstream, midstream, and downstream areas of the sub-watershed. The findings reveal that multi-stakeholder engagement including local communities, regional governments, businesses, and non-governmental organizations has driven significant socio-ecological transformations. Social-institutional changes are evident in the increased collective awareness among residents to establish and participate in river conservation communities, such as the Pusur Institute, which functions as a collaborative platform across actors. Ecologically, improvements are observed through conservation practices in upstream recharge areas, waste reduction through waste banks, eco-friendly agriculture, and river tubing activities, which have transformed the river into both an ecological and recreational asset. Economically, the development of alternative livelihoods such as conservation farming, river tourism, and waste bank initiatives has provided supplementary income for local communities. These findings suggest that Sub-Watershed management based on community participation and strengthened local institutions can serve as an effective strategy for achieving sustainable development at the local level.